2023
DOI: 10.1128/aac.00374-23
|View full text |Cite
|
Sign up to set email alerts
|

In-Class Cross-Reactivity among Hospitalized Patients with Hypersensitivity Reactions to Fluoroquinolones

Abstract: Results from this large, multicenter study suggest that patients with a confirmed ciprofloxacin, moxifloxacin, or levofloxacin hypersensitivity reaction are likely to tolerate other fluoroquinolones. Avoiding different fluoroquinolones in patients labeled with a ciprofloxacin, moxifloxacin, or levofloxacin allergy may not always be mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Shah et al's findings from a recent large, multicenter, retrospective study suggest that patients with confirmed ciprofloxacin, moxifloxacin, or levofloxacin HRs may tolerate other fluoroquinolones. Seventy percent of patients in the study were challenged with a different fluoroquinolones, but only nine (5.6%) patients experienced hypersensitivity [21]. Similarly to our patient, a case report published in Elsevier Espana in 2012 presents a patient who developed an anaphylactic reaction to levofloxacin, but tolerated ciprofloxacin four weeks afterwards [22].…”
Section: Discussionsupporting
confidence: 73%
“…Shah et al's findings from a recent large, multicenter, retrospective study suggest that patients with confirmed ciprofloxacin, moxifloxacin, or levofloxacin HRs may tolerate other fluoroquinolones. Seventy percent of patients in the study were challenged with a different fluoroquinolones, but only nine (5.6%) patients experienced hypersensitivity [21]. Similarly to our patient, a case report published in Elsevier Espana in 2012 presents a patient who developed an anaphylactic reaction to levofloxacin, but tolerated ciprofloxacin four weeks afterwards [22].…”
Section: Discussionsupporting
confidence: 73%